Broadband Photodetection: 2D Silicon‐Based Semiconductor Si2Te3 toward Broadband Photodetection (Small 13/2021). Issue 13 (1st April 2021) - Chen, Jiawang; Tan, Chaoyang; Li, Gang; Chen, Lijie; Zhang, Hanlin; Yin, Shiqi; Li, Ming; Li, Liang; Li, Guanghai
Abstract : In article number 2006496, Liang Li, Guanghai Li, and co‐workers synthesize silicon‐based semiconductor Si2 Te3 crystals using a chemical vapor deposition technique. The combined features of silicon and layered structure bridge the 2D materials family and silicon‐based materials family together, while the intrinsic defects in Si2 Te3 yield ultrawide photoluminescence spectra and broadband spectral response from 405 nm up to 1064 nm.